2010
DOI: 10.1002/emmm.201000084
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of transglutaminase 2 mitigates transcriptional dysregulation in models of Huntington disease

Abstract: Caused by a polyglutamine expansion in the huntingtin protein, Huntington's disease leads to striatal degeneration via the transcriptional dysregulation of a number of genes, including those involved in mitochondrial biogenesis. Here we show that transglutaminase 2, which is upregulated in HD, exacerbates transcriptional dysregulation by acting as a selective corepressor of nuclear genes; transglutaminase 2 interacts directly with histone H3 in the nucleus. In a cellular model of HD, transglutaminase inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
134
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(144 citation statements)
references
References 91 publications
(143 reference statements)
8
134
0
Order By: Relevance
“…Approximately 0.3 µM ZDON was enough for complete inhibition of the isopeptidase activity which is in a good correlation with the expected value in case of an irreversible inhibitor in the presence of 0.3 µM TG2 although the apparent IC50 value was 30.7 nM (calculated by fitting a dose-response curve hypothesising standard slope) which is lower than a reported one in an in vitro transamidation assay [24].…”
Section: Potential Applications Of the Newly Developed Kinetic Isopepsupporting
confidence: 75%
See 1 more Smart Citation
“…Approximately 0.3 µM ZDON was enough for complete inhibition of the isopeptidase activity which is in a good correlation with the expected value in case of an irreversible inhibitor in the presence of 0.3 µM TG2 although the apparent IC50 value was 30.7 nM (calculated by fitting a dose-response curve hypothesising standard slope) which is lower than a reported one in an in vitro transamidation assay [24].…”
Section: Potential Applications Of the Newly Developed Kinetic Isopepsupporting
confidence: 75%
“…However, the effects of newly developed inhibitors were always tested on the crosslinking activity of TG2 and there has been no comparison of their effect on isopeptidase activity of TG2, particularly in a kinetic, protein substrate assay that has not existed so far. A commercially available, cell permeable, irreversible active site directed inhibitor of TG2, the ZDON (Zedira, [24]) was tested in our newly developed method (Fig. 2C).…”
Section: Potential Applications Of the Newly Developed Kinetic Isopepmentioning
confidence: 99%
“…We have recently shown that these enzymes also modulate transcription. 5 Inhibition of their activity leads to normalization of genes repressed in neurodegenerative conditions and subsequently neuroprotection. There is an increase in TG transamidating activity in different models of stroke [6][7][8][9] and inhibition of TG with an FDA approved, nonselective inhibitor, cystamine, showed beneficial effects.…”
Section: Transglutaminases: New Epigenetic Kids On the Cns Blockmentioning
confidence: 99%
“…Accordingly, TG2 is upregulated in cerebellar granule cells exposed to NMDA toxicity 64 and its inhibition in medium-sized spiny neurons derived from HD mice (YAC128) or wild-type controls is sufficient to protect neurons from NMDA-mediated toxicity. 5 A putative mechanism by which the inhibition of TG activity halts excitotoxic death could involve the derepression of peroxisome proliferator-activated receptor-g coactivator-1d expression. 5 Indeed, it has been recently reported that peroxisome proliferator-activated receptor-g coactivator-1d blocks extrasynaptic NMDA receptor activity and excitotoxicity in models of HD.…”
Section: Pathologic Gene Repression After Stroke: Excitotoxicity Cytmentioning
confidence: 99%
See 1 more Smart Citation